Ultrathin anatase TiO2 nanosheets embedded with TiO2-B nanodomains for lithium-ion storage : capacity enhancement by phase boundaries - Wu, Qili (2015)
A new form of TiO2 microspheres comprised of anatase/TiO2-B ultrathin composite nanosheets has been synthesized successfully and used as Li-ion storage electrode material. By comparison between samples obtained with different annealing temperatures, it is demonstrated that the anatase/TiO2-B coherent interfaces may contribute additional lithium storage venues due to a favorable charge separation at the boundary between the two phases. The as-prepared hierarchical nanostructures show capacities of 180 and 110 mAh g−1 after 1000 cycles at current densities of 3400 and 8500 mA g−1. The ultrathin nanosheet structure which provides short lithium diffusion length and high electrode/electrolyte contact area also accounts for the high capacity and long-cycle stability.